Step‐Wise Chondrogenesis of Human Induced Pluripotent Stem Cells and Purification Via a Reporter Allele Generated by CRISPR‐Cas9 Genome Editing. (31st October 2018) - Adkar, Shaunak S.; Wu, Chia‐Lung; Willard, Vincent P.; Dicks, Amanda; Ettyreddy, Adarsh; Steward, Nancy; Bhutani, Nidhi; Gersbach, Charles A.; Guilak, Farshid
Abstract: The differentiation of human induced pluripotent stem cells (hiPSCs) to prescribed cell fates enables the engineering of patient‐specific tissue types, such as hyaline cartilage, for applications in regenerative medicine, disease modeling, and drug screening. In many cases, however, these differentiation approaches are poorly controlled and generate heterogeneous cell populations. Here, we demonstrate cartilaginous matrix production in three unique hiPSC lines using a robust and reproducible differentiation protocol. To purify chondroprogenitors (CPs) produced by this protocol, we engineered a COL2A1‐GFP knock‐in reporter hiPSC line by CRISPR‐Cas9 genome editing. Purified CPs demonstrated an improved chondrogenic capacity compared with unselected populations. The ability to enrich for CPs and generate homogenous matrix without contaminating cell types will be essential for regenerative and disease modeling applications.Stem Cells 2019;37:65–76 Abstract :